2010
DOI: 10.1111/j.1468-036x.2009.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Value of Corporate Eco-Efficiency

Abstract: This study adds new insights to the long-running corporate environmentalfinancial performance debate by focusing on the concept of eco-efficiency. Using a new database of eco-efficiency scores, we analyse the relation between ecoefficiency and financial performance from 1997 to 2004. We report that ecoefficiency relates positively to operating performance and market value. Moreover, our results suggest that the market's valuation of environmental performance has been time variant, which may indicate that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
329
4
24

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(382 citation statements)
references
References 45 publications
25
329
4
24
Order By: Relevance
“…These studies, however, fail to provide clear-cut empirical evidence on whether SRI does yield higher returns after adjusting for risks. Similarly, studies on (b) ratings [46][47][48], and (c) screenings [49] in terms of sustainability, do not seem to provide clear cut evidence in terms of higher returns either. Studies of (d) predictability and determinants of returns and volatility [50,51], highlight the role of various forms of uncertainties related to economic policies; and (e) co-movements of SRI indexes and with conventional indexes across various regions [1,52] have been shown to exist, especially when nonlinearity is taken into account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies, however, fail to provide clear-cut empirical evidence on whether SRI does yield higher returns after adjusting for risks. Similarly, studies on (b) ratings [46][47][48], and (c) screenings [49] in terms of sustainability, do not seem to provide clear cut evidence in terms of higher returns either. Studies of (d) predictability and determinants of returns and volatility [50,51], highlight the role of various forms of uncertainties related to economic policies; and (e) co-movements of SRI indexes and with conventional indexes across various regions [1,52] have been shown to exist, especially when nonlinearity is taken into account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One approach would be using Tobin's Q (which is typically proxied by calculating the firm's market value to book asset value ratio) to compare the Q-ratios of high and low CSR firms, and this is the approach taken in Guenster et al (2011). However, this measure has several shortcomings.…”
Section: Analysis Of the Impact Of Csr On Firm Valuementioning
confidence: 99%
“…To understand the total financial implications of CSP it is therefore necessary for attention to be given to both stock returns and firm value. Relatively few studies have based their estimations on firm value but recent studies that have used this concept (Guenster et al, 2011;Jo and Harjoto, 2011;Kim and Statman, 2012;Gregory and Whittaker (forthcoming)) find evidence of CSR indicators being positively related to firm value. In this paper we extend this literature with an investigation of the means by which CSR strategies might impact on value.…”
Section: Introductionmentioning
confidence: 99%
“…Data from Innovest Strategic Value Advisors used more than 60 quantitative and qualitative criteria to measure ecoefficiency. The results of the study by Guenster et al (2006) stated that companies with ecoefficiency had a higher Return on Assets (RoA) and market value. Sinkin et al (2008) showed that increasing the effectiveness of business processes and simultaneously reducing the environmental impact would increase the value of the US companies.…”
Section: Previous Relevant Studies and Hypothesismentioning
confidence: 99%